Case Report: Variegate porphyria disclosed by post-gastric bypass complications and causing predominant painful sensorimotor axonal peripheral neuropathy - Collaud, Edwige; Wittwer, Luis; Minder, Anna-Elisabeth; Annoni, Jean-Marie; Minder, Elisabeth I.; Chabwine, Joelle N. (Frontiers in Genetics, 2022)
Background and aims: Porphyrias constitute a group of rare genetic diseases due to various, mostly autosomal dominant mutations, causing enzymatic deficiency in heme biosynthesis. As a result, neurotoxic porphyrin precursors and light-sensitive porphyrins accumulate, while dysfunction in their targets determines the disease symptoms. Variegate porphyria (VP), one of the acute hepatic porphyrias, is caused by a protoporphyrinogen oxidase (PPOX) mutation. During acute attacks, among other factors, triggered by drugs, stressors, or fasting, an increase in urinary and fecal porphobilinogen (PBG), aminolevulinic acid (ALA), and porphyrins occurs, damaging the autonomous, peripheral, or central nervous system. The disease remains often latent or displays minimal symptoms usually overlooked, exposing undiagnosed patients to potentially serious complications in the presence of the aforementioned triggers. Case report: This 46-year-old woman presented, some days after a bariatric surgery, with severe flaccid tetraparesis and neuropathic pain, initially misdiagnosed as a functional neurological disorder. The severe axonal sensorimotor polyneuropathy led to further investigations, disclosing high urinary porphobilinogen, ALA, and porphyrin levels due to a new PPOX mutation. Retrospectively, it appeared that the patient had had typical VP symptoms (abdominal pain, fragile skin, and dark urine episodes) for years prior to the surgery. Treated with carbohydrate load, neurorehabilitation, and analgesics, she slowly recovered to full mobility, with partial autonomy in her daily life activities, although fatigue and severe pain persisted, preventing her from returning to work. Conclusion: This case documents gastric bypass surgery as a trigger of severe VP invalidating neurological symptoms and illustrates how the delayed diagnosis and post-interventional complications could have been prevented by screening for porphyria cardinal symptoms prior to the intervention. Likewise, this cost-effective screening should be performed before any treatment influencing the diet, which would dramatically improve the porphyria diagnosis rate and outcome.